Role of mutation independent constitutive activation of FLT3 in juvenile myelomonocytic leukemia - Andrica C.H. de Vries; Ronald W. Stam; Pauline Schneider; Charlotte M. Niemeyer; Elisabeth R. van Wering; Oskar A. Haas; Christian P. Kratz; Monique L. den Boer; Rob Pieters; Marry M. van den Heuvel-Eibrink (Haematologica, 2007)
FLT3 gene mutations have been identified as prognostic factors in myeloid malignancies. Furthermore, FLT3 can be activated by wild type overexpression or ligand-dependent in leukemic cells co-expressing FLT3 ligand (FLT3L). So far no data are available on FLT3/FLT3L expression and activation in JMML. In 51 clinical JMML samples, activating mutations were screened, FLT3 and FLT3L mRNA levels were assessed and the sensitivity of JMML cells to the FLT3 inhibitor PKC412 was tested by MTT assays. No evidence for constitutively activation of FLT3/FLT3L was found in JMML, indicating that FLT3 inhibitors are unlikely to be effective in JMML.